1990
DOI: 10.1111/j.1464-5491.1990.tb01432.x
|View full text |Cite
|
Sign up to set email alerts
|

Leucocyte Mobilization and Release of Neutrophil Elastase Following Acute Insulin‐induced Hypoglycaemia in Normal Humans

Abstract: Insulin-induced hypoglycaemia in humans is associated with the rapid mobilization of leucocytes in peripheral blood. The aim of the present study was to determine whether neutrophil activation, manifested in plasma by neutrophil elastase concentration, occurs in response to insulin-induced hypoglycaemia. Acute hypoglycaemia (mean blood glucose 1.3 +/- 0.2 mmol l-1; mean +/- SD) was induced with intravenous insulin in 15 normal human subjects, and provoked an increase in the neutrophil count from 3.4 (range 1.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 16 publications
0
26
1
Order By: Relevance
“…Both factors are known to increase WBC counts by increasing neutrophil influx from marrow storage and decreasing efflux from the blood stream (32,33). In addition, cortisol and insulin may increase the WBC count by stimulating leptin secretion from adipocytes (34).…”
Section: Discussionmentioning
confidence: 99%
“…Both factors are known to increase WBC counts by increasing neutrophil influx from marrow storage and decreasing efflux from the blood stream (32,33). In addition, cortisol and insulin may increase the WBC count by stimulating leptin secretion from adipocytes (34).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoglycemia induces a hypercoagulant state in humans via increased platelet aggregation and changes in plasma concentrations of coagulation factors. 12,13,38,39 For example, it has been shown that factor VIII was increased 2-fold after 30 minutes of hypoglycemia. 13 Hypoglycemia may also be responsible for initiating an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…In 1 study, hypoglycemia was associated with a 3-fold increase in the neutrophil count and an elevation in neutrophil elastase, a potent proteolytic enzyme. 39 Long-QT syndrome is well recognized as being associated with an increased risk of sudden cardiac death. 40 More worryingly, acute hypoglycemia has been demonstrated to produce prolongation of the corrected QT interval by up to 35% in patients with type 1 DM, with values reaching Ͼ550 milliseconds.…”
Section: Discussionmentioning
confidence: 99%
“…Strict glycaemia control using intensive insulin therapy increases the risk of hypoglycaemia. While it is well known that hypoglycaemia affects cognition, mood and consciousness, it also has profound effects on blood constituents [7,8], inflammatory cytokine level [9,10], and coagulation and fibrinolysis factors [11,12], mainly through the sympathoadrenal response to hypoglycaemia. These data suggest that hypoglycaemia induced by insulin injection may be implicated in the progression of atherosclerosis; however, there are no convincing in vivo data in support of this hypothesis.…”
Section: Introductionmentioning
confidence: 99%